The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fphys.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heart rate on Basketball Three-Point Shot Accuracy

Abstract: The three-point shot (3S) is a fundamental basketball skill used frequently during a game, and is often a main determinant of the final result. The aim of the study was to investigate the effect of different metabolic conditions, in terms of heart rates, on 3S accuracy (3S%) in 24 male (Under 17) basketball players (age 16.3 ± 0.6 yrs). 3S performance was specifically investigated at different heart rates. All sessions consisted of 10 consecutive 3Ss from five different significant field spots just beyond the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to specifically examine the variation in JS% induced by exercise intensity. These results are in line with those of previous research on the effect of exercise intensity on FT ( Padulo et al, 2015a ; Mokou et al, 2016 ) and three-point shot (3S) accuracy ( Ardigò et al, 2018 ), which showed a significant reduction in shot accuracy at 80HR compared to 0HR and 50HR. Thus, exercise intensity exerted a similar effect on the 3S, JS, and FT, yet, a difference can be identified between the 3S and JS compared with the FT. Namely, FT is not a game-play flow-driven basketball fundamental, given that it is basically shot without any defence pressure and during a game-play pause.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, the present study is the first to specifically examine the variation in JS% induced by exercise intensity. These results are in line with those of previous research on the effect of exercise intensity on FT ( Padulo et al, 2015a ; Mokou et al, 2016 ) and three-point shot (3S) accuracy ( Ardigò et al, 2018 ), which showed a significant reduction in shot accuracy at 80HR compared to 0HR and 50HR. Thus, exercise intensity exerted a similar effect on the 3S, JS, and FT, yet, a difference can be identified between the 3S and JS compared with the FT. Namely, FT is not a game-play flow-driven basketball fundamental, given that it is basically shot without any defence pressure and during a game-play pause.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, several studies have been conducted recently to develop sport-specific exercise tests (e.g., including uni- or multi-directional repeated sprints) in order to match the metabolic demands and activity patterns of basketball ( Attene et al, 2015b , 2016 ; Padulo et al, 2015b , 2016 ; Zagatto et al, 2017 ), whereas other studies have examined the effectiveness of sport-specific training interventions ( Attene et al, 2014 , 2015a ). Although the physical, physiological and psychological characteristics, tactical and nutritional aspectis, commonly considered as key components for successful basketball performance, have already been investigated, less information is available on technical skills, such as the shooting task ( Padulo et al, 2015a ; Ardigò et al, 2018 ). It has been supported ( Okazaki et al, 2015 ) that the ability to shoot a jump-shot (JS) is a major component of sport performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is safe to assume that they had high levels of endurance and were used to short recovery periods from intermittent bouts of intense basketballspecific activity. Furthermore, previous research suggests no significant effect of fatigue on free throw, jump shot or threepoint shooting performance, when comparing moderate (50% Max-HR) and high (80% Max-HR) levels of fatigue (Ardigò, Kuvacic, Iacono, Dascanio, & Padulo, 2018;Padulo et al, 2015;Uygur, Goktepe, Ak, Karabörk, & Korkusuz, 2010).…”
Section: Free Throw • Calibration • Nba • Basketball • Warm-up Decrementmentioning
confidence: 89%
“…A modern basketball player of high qualification is an athlete with a high level of development of jumping, speed, endurance strength, which reaches the level of development of these qualities in multi-player athletes. But in basketball, the athletic qualities should be organically combined with lightning-fast technique, high accuracy of target actions, which are manifested in the precision of the hits of the ball to the basket (Ardigo, Kuvacic, Iacono, Dascanio, & Padulo, 2018;Chen, Wu, Lo, Chen, Yang, Huang, & Liu, 2018;Kozina, Sobko, Vilvitsky, Xiaofei, Tymko, Glyadya, & Minak, A., 2018).…”
Section: Introductionmentioning
confidence: 99%